Light absorption and utilization by colonies of the congeneric hermatypic corals Montastraea faveolata and Montastraea cavernosa - Michael P.Lesser Lesser; Charles Mazel; David Phinney; Charles S. Yentsch (Limnology and Oceanography, 2000)
The congeneric species Montastraea faveolata and Montastraea cavernosa are important hermatypic corals on reefs throughout the Bahamas, Caribbean, and the Florida reef tract that have overlapping bathymetric distributions. However, these congeners differ in their respective abundance at similar depths. The underlying mechanism for these patterns may partly be because of their relative dependence on photoautotrophy versus heterotrophy. The dependence of these two corals on photoautotrophy was examined quantifying the optical properties and productivity of these two species of corals at two different depths in the Dry Tortugas. Maximum surface irradiances in the Dry Tortugas during this study varied from 1,900 to 2,100 μmol quanta m ‐2 s ‐1 . Spectral attenuation coefficients calculated from the 1995 and 1996 irradiance data differed by as little as 10% within the visible wavelengths (photosynthetically active radiation [PAR], 400–700 nm), suggesting year‐to‐year similarities in the optical prop‐erties of the overlying water column. Underwater irradiances of PAR were ∼400 μmol quanta m −2 s −1 and 25 μmol quanta m ‐2 s ‐1 at 10 m and 18 m, respectively. Significantly lower rates of maximum photosynthesis were observed for samples of M. cavernosa compared with M. faveolata at 10 m and 18 m. For samples of M. faveolata from both depths, the mean chlorophyll‐specific absorption (a*) across all PAR wavelengths was greater than that of M. cavernosa . When spectrally corrected for the underwater light field and used to calculate the minimum quantum requirements (1/_m) of these corals at each depth, we observed that M. faveolata always had higher 1/_m than M. cavernosa (50 versus 18 quanta O 2 −1 and 39 versus 15 quanta O 2 ‐1 at 10 m and 18 m, respectively.) M. cavernosa , with its greater pigment concentrations and lower a *, exhibits a significant package effect that results in a smaller functional optical cross section and lower maximum photosynthetic capacities, whereas M. faveolata at the same depths, despite the greater minimum quantum requirements, has a larger functional optical cross section and enhanced absorption of available visible radiation, resulting in a greater maximum photosynthetic capacity. Based on polyp size, corallite structure, and surface area considerations, M. faveolata appears to depend on pho‐toautotrophy versus heterotrophy to a greater extent than its congener, M. cavernosa . Recent data suggest, however, that polyp size alone may not be a good indicator for differences in trophic strategies and that coordinated studies on feeding and productivity in corals are needed to better understand their ecological distributions.